Republic of Azerbaijan : Staff Report for the 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2012)
Strong fiscal stimulus in Azerbaijan continued in 2011 triggered by unanticipated increases in global oil prices. The 2011 Article IV Consultation highlights that near and medium-term economic prospects are favorable and nonhydrocarbon growth could reach 6 percent in 2012. Executive Directors have endorsed that significant actions would be needed for Azerbaijan to maintain the record of high growth and significant poverty reduction. Given the limited horizon of hydrocarbon resources, the economy needs to be reoriented from its symbiotic dependence on natural resource revenues.